Implementation of Surveillance robot with the feature of semi automatic recharging capability (International Journal of Engineering and Computer Science, 2015)
This paper presents the design and implementation of a surveillance system with semi automatic battery recharging capability for the prolonged activities of robots. A battery recharge station is proposed to implement battery off‐line recharging when it’s drained. The surveillance robot is a wheeled robot with an onboard camera and a rechargeable battery case in the front. It communicates with the user wirelessly through Wi-Fi network. As the system powered up the surveillance robot will move across the area avoid obstacles using infra red sensor and by exporting the battery voltage values over web for user reference, when on board battery is low then the threshold value, the robot will stop then the user can route the robot to the docking station using web based controls. After the battery is completely charged the robot will be unlocked from docking station and continuous its surveillance. The experimental results show that the system is working with 95% accuracy. The proposed system is proved to be efficient in security applications that need the robots to work continuously over a long period.